The Private Security Events Database. (September 2019) - Avant, Deborah; Neu, Kara Kingma
Since the 1990s, the private provision of military and security services has become a common feature of local, national, and transnational politics. The prevalence of private security has generated important questions about its consequences, but data to answer these questions are sparse. In this article, we introduce the Private Security Events Database (PSED) that traces the involvement of private military and security companies (PMSCs) in events in Africa, Latin America, and Southeast Asia from 1990 to 2012. We describe the PSED project, highlight its descriptive findings, conduct a replication and reanalysis of Akcinaroglu and Radziszewski's contract data in Africa, and compare the two databases' coverage of Sierra Leone from 1991 to 1997. Our analysis demonstrates new insights into the relationship between PMSCs and civil war duration, confirming a correlation between PMSC presence and shorter conflicts, but questioning the logic Akcinaroglu and Radziszewski propose. It also points to a number of productive paths for future research.